Effects of culture conditions on isolated microspore culture of melon (Cucumis melo L.) - Minh Ly Nguyen; Ton Nu Bao Tien Huyen (Vietnam Journal of Science, Technology and Engineering, 2023)
Isolated microspore culture is a useful tool to produce pure, fully homozygous parental lines in a short time. This study evaluated factors including the microspore developmental stage, cell culture density, and heat treatment influencing callus formation from melon microspores (Cucumis melo L.). The results showed that the obtained number of calli induced was highest (11.00±1.02) when cultivating flower buds with sizes 7.0-7.9 mm that contained microspores at middle-to-late uninucleate stages. The optimal microspore density for culture is 4×104 cells. The cultured medium was NLN, containing 130 g/l of sucrose at pH 5.8. Heat treatment at 40ºC for 48 hours was best suited for callus induction of all flower bud sizes. The survival rate of microspores after 7 days of culture was lower than before inoculation and was only 75.6%. The development of the microspores and the arising of calli and embryos have been observed and evaluated for morphological cell characteristics. However, in this study, no mature embryo formation or seedling regeneration was observed.